2017
DOI: 10.1007/s13280-016-0867-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability in surface energy balance across tundra, snow and ice in Greenland

Abstract: The surface energy balance (SEB) is essential for understanding the coupled cryosphere–atmosphere system in the Arctic. In this study, we investigate the spatiotemporal variability in SEB across tundra, snow and ice. During the snow-free period, the main energy sink for ice sites is surface melt. For tundra, energy is used for sensible and latent heat flux and soil heat flux leading to permafrost thaw. Longer snow-free period increases melting of the Greenland Ice Sheet and glaciers and may promote tundra perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…We expect strong release of the heat, which was added to the lake within our study period, during late summer and autumn before refreeze (see Petrone & Rouse, ; Rouse et al, ), a period we did not cover with our measurements. High Res for the ice cover period (frozen: 34.1 W/m 2 ; melting: 201.0 W/m 2 ) confirmed that the energy required for ice cover melt represents an important EB component (Lund et al, ). The back‐calculation resulted in a slightly overestimated initial ice thickness but an ice decay rate during the melting ice cover period which is comparable to other studies (e.g., 1.5 cm/day for boreal lake, Jakkila et al, ; 6–10 cm/day for floating ice lakes, 11–16 cm/day for bedfast ice lakes in Northern Alaska, Arp et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…We expect strong release of the heat, which was added to the lake within our study period, during late summer and autumn before refreeze (see Petrone & Rouse, ; Rouse et al, ), a period we did not cover with our measurements. High Res for the ice cover period (frozen: 34.1 W/m 2 ; melting: 201.0 W/m 2 ) confirmed that the energy required for ice cover melt represents an important EB component (Lund et al, ). The back‐calculation resulted in a slightly overestimated initial ice thickness but an ice decay rate during the melting ice cover period which is comparable to other studies (e.g., 1.5 cm/day for boreal lake, Jakkila et al, ; 6–10 cm/day for floating ice lakes, 11–16 cm/day for bedfast ice lakes in Northern Alaska, Arp et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Zackenberg station represents high-Arctic conditions in central north-east Greenland (74°28′N, 20°34′W, annual mean temperature −9°C between 1996−2015) and Disko Island represents low-Arctic conditions on an island in mid-south-west Greenland (69°15′N, 53°34′W, annual mean temperature −3.1°C between 1991−2015). Temperature measurements were obtained from climate measurement masts, methane fluxes from automatic chamber (AC) measurements and latent and sensible heat fluxes from eddy covariance measurements from Nuuk and Zackenberg (Pirk et al 2017, Lund et al 2017. AC measurements are only available since 2006 and 2008 from Zackenberg and Nuuk respectively.…”
Section: Temperature and Surface Flux Observationsmentioning
confidence: 99%
“…The study site is located within a Cassiope tetragona tundra heath, dominated by C. tetragona, Dryas integrifolia and Vaccinium uliginosum, with patches of mosses. Several studies on soil and permafrost (Palmtag et al, 2015;Westermann et al, 2015), surface energy balance (Lund et al, 2014;Stiegler et al, 2016;Lund et al, 2017) and carbon exchange (Mastepanov et al, 2008;Lund et al, 2012;Elberling et al, 2013) have been published based on data from this site. A rich dataset is available from this site through the extensive, cross-disciplinary Greenland Ecosystem Monitoring programme (www.g-e-m.dk).…”
Section: Zackenbergmentioning
confidence: 99%